At-risk youth receive similar benefits from equine- assisted psychotherapy and traditional psychotherapy; an applied analysis - McCrea, Cindy E.; Tibbets, Grace; Smith, Levi W.; Campbell, Cynthia G. (Frontiers in Psychiatry, 2025)
IntroductionEquine-assisted psychotherapy (EAP) is a promising modality for the treatment of emotional difficulties in youth. Few studies have compared the benefits of EAP to those of traditional psychotherapy for at-risk youth in community-based settings.MethodWe compare the effectiveness of individually administered EAP and traditional psychotherapy (TP) for improving adolescent mental health using data from a community-based participatory research partnership. Adolescent clients who were referred to a community-based non-profit agency for services related to emotional and behavioral difficulties comprised the sample (N = 94, mean age at intake was 14.33 years). We compared the improvement in mental health outcomes between intake and follow-up for participants who received weekly, individual TP (N = 65) with those who received weekly, individual EAGALA-certified EAP (N = 29). Licensed mental health professionals administered treatments (mean treatment period of 241 days).ResultsOn average, clients’ global psychological, social, and emotional wellness scores on the Mental Health Continuum improved by 18-23%. Clients’ resilience, self-efficacy, social and emotional skills, perceptions of hope, and cognitive reappraisal skills also improved significantly (12% to 28%) with one exception; average emotion suppression scores did not change across the treatment period in either group (p = .77). Mixed linear models revealed that clients receiving EAP and TP experienced similar levels of improvement in all dimensions.DiscussionThese quasi-experimental data confirm that community-based non-profit programs that offer psychotherapy benefit at-risk youth and indicate that EAP and TP may provide similar benefits to struggling youth.